2011
DOI: 10.1111/j.1365-2109.2011.03016.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and growth of the sea cucumberHolothuria leucospilotaBrandt: a comparison between suspended and bottom cultures in a subtropical fish farm during summer

Abstract: Survival and growth of the sea cucumberHolothuria leucospilota Brandt: a comparison between suspended and bottom cultures in a subtropical fish farm during summer Abstract The feasibility of co-culturing the sea cucumber Holothuria leucospilota Brandt in a subtropical fish farm was investigated in a field study. Sea cucumbers were cultured in the fish farm in cages suspended at 4 m deep (suspended culture) and directly on the seafloor (bottom culture). The survival and growth of the sea cucumbers were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 22 publications
3
41
0
1
Order By: Relevance
“…Gao et al (2011) also found that muddy material collected from suspended organic detritus from natural seawater is favorable for the growth of sea cucumbers. Similarly, the food assimilation efficiency of sea cucumber Holothuria leucospilota feeding on natural sediment (17.7-68.3 %) was much higher than that of animals feeding on fish farm detritus (14.9 %) (Yu et al 2013). These results indicate that survival and growth performance of juvenile sea cucumber are enhanced by the consumption of natural sea mud, possibly as a result of sea mud functioning as a digestive aid.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Gao et al (2011) also found that muddy material collected from suspended organic detritus from natural seawater is favorable for the growth of sea cucumbers. Similarly, the food assimilation efficiency of sea cucumber Holothuria leucospilota feeding on natural sediment (17.7-68.3 %) was much higher than that of animals feeding on fish farm detritus (14.9 %) (Yu et al 2013). These results indicate that survival and growth performance of juvenile sea cucumber are enhanced by the consumption of natural sea mud, possibly as a result of sea mud functioning as a digestive aid.…”
Section: Discussionmentioning
confidence: 90%
“…To supplement the wild harvest and to meet the increasing worldwide demand, intensive farming techniques for A. japonicus have been developed using ponds, sea pens, and sea bottoms (Chen 2003(Chen , 2005Yu et al 2013Yu et al , 2014. However, ecologically sustainable techniques for culture of this species, especially for the post-nursery culture of A. japonicus, have not yet been fully developed.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, heavy organic and sulphide pollution has been reported in the sediment of the fish farms (Yu, Hu, Zhou, Li & Peng 2013). In recent years, heavy organic and sulphide pollution has been reported in the sediment of the fish farms (Yu, Hu, Zhou, Li & Peng 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The self‐pollution of abalone aquaculture could be reduced via the development of integrated multitrophic aquaculture (IMTA) farming pattern by introducing the deposit‐feeding sea cucumber to the abalone monoculture system. Sea cucumbers can feed on sediment with organic matter and play a key role in reducing nutrient loads to the environment (Ahlgren ; Michio et al ; Yu et al ). It was reported that the dissolved nitrogen in the water of abalone tanks was reduced when co‐cultured with sea cucumber, mainly because the organic matter was ingested and assimilated by the sea cucumber (Kang et al ; Wang et al ).…”
mentioning
confidence: 99%